Profil Pasien dengan Delirium yang Dirawat di Intensive Care Unit RSUP Prof. Dr. R. D. Kandou Manado Periode Juli 2024 – Juli 2025 - Yana, Ruth D.; Laihad, Mordekhai L.; Kambey, Barry I. (e-CliniC, 2026)
Abstract: Delirium is a disorder of attention and consciousness. It is a common complication in critically ill patients. Delirium is associated with poor clinical outcomes. Data on the characteristics of delirium patients in Indonesia, particularly in North Sulawesi, are still limited. This study aimed to determine the profile of patients with delirium treated in the Intensive Care Unit (ICU) of Prof. Dr. R. D. Kandou General Hospital, Manado, from July 2024 – July 2025. This was a descriptive observational study with a retrospective design. The results showed that out of the 1,029 ICU patients during the study period, there were 45 patients (4.37%) were included as samples. The majority of patients were aged 18–59 years (66.67%) and male (68.89%). The most common RASS score was -2 (20%), indicating a predominance of low-activity delirium. The most common diagnoses were postoperative (35.56%) and sepsis (22.22%). The ICU mortality rate was 33.33%. The average length of stay was 10.73 days with a median of 9 days. In conclusion, the incidence of delirium in the Intensive Care Unit of Prof. Dr. R. D. Kandou General Hospital was 4.37%. The majority occurred in adults, males, with a tendency toward hypoactive delirium. Post-operative conditions and sepsis were the most common diagnoses. Mortality and length of stay were relatively high. Keywords: delirium; Intensive Care Unit; RASS score    Abstrak: Delirium merupakan gangguan pada perhatian dan kesadaran yang sering menjadi komplikasi pada pasien kritis. Delirium berkaitan dengan luaran klinis yang buruk. Data mengenai karakteristik pasien delirium di Indonesia, khususnya di Sulawesi Utara, masih terbatas. Penelitian ini bertujuan untuk menentukan profil pasien dengan delirium yang dirawat di Intensive Care Unit (ICU) RSUP Prof. Dr. R. D. Kandou Manado periode Juli 2024–Juli 2025. Jenis penelitian ialah deskriptif observasional dengan desain retrospektif. Hasil penelitian mendapatkan bahwa dari 1.029 pasien ICU dalam periode penelitian, terdapat 45 pasien (4,37%) yang termasuk dalam sampel penelitian. Mayoritas pasien berusia 18–59 tahun (66,67%) dan berjenis kelamin laki-laki (68,89%). Skor RASS terbanyak ialah -2 (20%), yang menunjukkan dominasi delirium dengan aktivitas rendah. Diagnosis terbanyak ialah pascaoperasi (35,56%) dan sepsis (22,22%). Tingkat mortalitas di ICU ialah 33,33%. Rerata length of stay (LOS) ialah 10,73 hari dengan median sembilan hari. Simpulan penelitian ini ialah angka kejadian delirium di ICU RSUP Prof. Dr. R. D. Kandou Manado ialah 4,37%. Mayoritas terjadi pada usia dewasa, laki-laki, dengan kecenderungan delirium hipoaktif. Kondisi pascaoperasi dan sepsis merupakan diagnosis yang paling banyak ditemukan. Angka kematian dan lama rawat inap masih relatif tinggi. Kata kunci: delirium; Intensive Care Unit; RASS score